Аутплейсмент персоналу як необхідний елемент кадрової політики - Lopatynskyi, Yurii; Liubov, Vodianka (ТОВ ВД «Гельветика» 73034, Україна, м. Херсон, вул. Паровозна, буд. 46-А Тел.: +38 (0552) 39-95-80 e-mail: mailbox@helvetica.com.ua, 2021)
The article considers the essence of outplacement as a necessary element of personnel policy. The urgency of this issue arose acutely in a pandemic that has spread around the world, causing a global crisis. Businesses lay off workers en masse because they are unable to pay them wages, and therefore outplacement is a much-needed means of severing the relationship between owners and employees. It is aimed not only to preserve the reputation of the enterprise, but also to ensure the smooth exit of the dismissed employee from the enterprise and its further employment. The main directions of outplacement offered by recruitment companies for enterprises are described. The advantages and disadvantages of using outplacement are identified, the importance of maintaining the image for a company that aims to humanely suspend the contract with redundant employees is described. The future actions of employees who were fired from the organization and how it may affect the company's activities are analyzed. The attitude of Ukrainian companies to outplacement and how often they use it are determined. The most important criteria for decision-making by the company, which decided to use the outplacement service at the global level, were identified - among which are - maintaining positive relationships with laid off employees, maintaining the company's image, reducing stress for redundant workers, helping to find new jobs. In order to disseminate outplacement services in Ukraine, it is necessary to constantly conduct surveys among employers to find out information about their attitude to this type of service, periodically collect statistics on the number of businesses providing outplacement services, the cost of these services, the number of customers. which was served by recruitment companies, periodically publish articles about outplacement, which describe its essence, content, advantages, disadvantages, as well as statistical information and customer feedback, follow the example of foreign companies and make outplacement a trend in human resource management.
Keywords: Аутплейсмент; рекрутингові компанії; скорочення персоналу; адпаптація